Gaps in asthma diagnosis and treatment in low- and middle-income countries - Barne, Monica (Frontiers in Allergy, 2023)
Low-and middle-income countries (LMICs) contribute to a major proportion of asthma morbidity and mortality globally, even though the prevalence is higher in high income countries. Mortality due to asthma is avoidable and patients should be able to live a near normal life. There are factors that influence overall disease prevalence and poor health outcomes due to asthma in LMICs. This article summarizes the gaps in asthma diagnosis and management in LMICs. The gaps are diverse. Each challenge needs to be addressed through policy decisions, upgrade of infrastructure, knowledge and skills for early diagnosis and correct management among health care providers, both clinicians and paramedics.Healthcare accessibility and affordability are genuine challenges, and the public healthcare system needs to be geared up to address these at primary and tertiary levels. Mass education of the population through national level government initiatives is needed to help bridge the sociocultural gaps.